A Multicenter Comparison of Open Versus Arthroscopic Fixation for Pediatric Tibial Spine Fractures. Issue 5 (31st May 2022) - Shimberg, Jilan L; Leska, Tomasina M; Cruz, Aristides I; Patel, Neeraj M; Ellis, Henry B; Ganley, Theodore J; Johnson, Ben; Milbrandt, Todd A; Aoyama, Julien T.; Fabricant, Peter D.; Green, Daniel W.; Kushare, Indranil; et al.
Background: When operative treatment is indicated, tibial spine fractures can be successfully managed with open or arthroscopic reduction and internal fixation. Hypothesis/Purpose: We hypothesized both approaches can lead to satisfactory outcomes for fracture healing, but that open treatment without preoperative advanced imaging can potentially lead to missed concomitant injuries. Methods: We performed an Institutional Review Board (IRB)-approved retrospective cohort study of pediatric tibial spine fractures presenting between January 1, 2000 and January 31, 2019 at 10 institutions. Patients were categorized into two cohorts based on treatment: arthroscopic reduction and internal fixation (ARIF) and open reduction and internal fixation (ORIF). Surgical outcomes, the incidence of concomitant injuries, and surgeon demographics were compared between groups. Results: There were 477 patients with tibial spine fractures who met inclusion criteria, 420 of whom (88.1%) were treated with ARIF, while 57 (11.9%) were treated with ORIF. Patients treated with ARIF were more likely to have an identified concomitant injury (41.4%) compared to those treated with ORIF (24.6%, p=0.021). Patients treated with ARIF were also more likely to have pre-treatment MRI (41.7% vs. 22.8%, p =0.010). Most concomitant injuries (74.5%) required surgical intervention. The most common treatment complications included arthrofibrosis (6.9% in ARIF patients, 7.0% in ORIF patients, p=1.00) and subsequent ACL injury (2.1% in ARIF patients and 3.5% in ORIF, p=0.86). The rate of complications, return to the operating room, and failure to return to full range of motion were similar between groups. Twenty surgeons with sports subspecialty training completed 85.0% of ARIF cases; the remaining 15.0% were performed by 12 surgeons without additional sports training. The majority (56.1%) of ORIF cases were completed by 14 surgeons without sports subspecialty training. Conclusion: This is the largest study comparing ARIF to ORIF in pediatric tibial spine fractures. This study demonstrated no difference in outcomes or nonunion following ARIF or ORIF for pediatric tibial spine fractures. There were significantly higher rates of concomitant injuries in patients treated with ARIF, however, these patients also had a higher rate of pre-treatment MRI. The majority of these concomitant injuries (74.5%) required surgical intervention. Pre-treatment MRI should be considered in the workup of tibial spine fractures to increase identification of concomitant injury. Concomitant injuries may be missed in tibial spine fractures treated with an open approach, especially in cases where preoperative advanced imaging is not obtained. Surgeon preference and training may impact treatment approach and identification and treatment of concomitant injury.